Desmoplastic fibroma of the mandible - Averna, R.; De Filippo, M.; Ferrari et al., S. (Acta Biomedica Atenei Parmensis, 2011)
We report the imaging findings of a desmoplastic fibroma (DF) of the mandible in a 3 years old girl. DF of bone is a rare, no-metastasizing but locally aggressive tumor. Hypercellularity, nuclear pleomorphism, mitotic activity, and traces of odontogenic epithelium and bony tissue are absent. US exam showed a highly vascular and well delimited mass, with no necrotic/hemorrhagic areas. It appeared as a well-defined osteolytic region in RX and a multiloculated, hypodense mass, with no periosteal reaction signs, in CT scans. MRI showed hypointensity in T1w TSE sequence and hyperintensity both in T1w TSE SPIR and T2w ones with no restriction of the “apparent diffusion coefficient” (ADC). In conclusion, remaining histology the gold standard for the DF diagnosis, imaging features may strongly suggest it.